Construction de l’intervention ergonomique. D’une préoccupation de montée en cadence à la décision d’investir pour transformer le travail : embûches et stratégies - Joffrey Beaujouan; Sophie Aubert; Fabien Coutarel (Perspectives Interdisciplinaires sur le Travail et la Santé)
A management team’s consent to invest in workplace changes is not systematically granted. From an ergonomist’s perspective, this raises questions about both the strategies to adopt and their effectiveness and limitations. This article presents an ergonomic intervention analysis based on an ergonomist’s narrative journal. The management team of an aircraft assembly line initially expressed a need to increase productivity. The results emphasize the importance of tacit strategies – whether or not they were anticipated by ergonomists – in the social and technical construction of an intervention. This article presents the viewpoint of an ergonomist who adopted a reflective approach to his practice. This reflexive approach did not focus on solving problems using a technical rationale, but rather on the social construction of solutions during the intervention. The analysis focuses on well-known patterns identified by ergonomists and enriches the professional practice’s existing system of references regarding competency. The study also contributes to the enrichment of the theoretical and methodological frameworks for qualitative analysis in the field of ergonomics from a pragmatic constructivist perspective.